Implementasi Peraturan Daerah Kabupaten Tabanan Nomor 9 Tahun 2014 Tentang Perizinan Bidang Kesehatan (Studi Kasus Izin Praktik Tenaga Medis di Kabupaten Tabanan) - Yulian, M. Rizky; Yudartha, I Putu Dharmanu; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2019)
ABSTRACT One of the health facilities in Tabanan Regency which is important to supporting development in the health sector is medical personnel. To guarantee its quality, every medical personnels in Tabanan Regency must have a practice license (SIP) and extend it if the practice license has expired as stipulated in Tabanan Regency Regional Regulation Number 9 of 2014 concerning Licensing in the Health Sector. However, there are still many medical personnels who do not have practice license (SIP) or have expired. Therefore, this study aims to find out how the implementation of Tabanan Regency Local Regulation Number 9 of 2014 (Case Study of practice license for Medical personnel in Tabanan Regency) by using descriptive qualitative methods with data collection techniques in the form of observation, interviews, and documentation, this research used descriptive qualitative methods. The results of this study indicate the implementation of Tabanan Regency Local Regulation Number 9 of 2014 Concerning Licensing in The Health Sector specially practice license for medical personnels in Tabanan Regency has not been running well because communication flow that has not been effective, inadequate resources, and SOPs that has not run optimally Keywords: Implementation, Practice License, Medical Personnel